![image](https://tex.z-dn.net/?f=+%5Cfrac%7Bx%5E%7B2%7D-6x%2B4%7D%7Bx-1%7D%3E0%2C+%5C%5C+x%5E2-6x%2B4%3D0%2C+D_1%3D5%2C+%5C%5C+x_1%3D3-%5Csqrt%7B5%7D%2C+x_2%3D3%2B%5Csqrt%7B5%7D%2C+%5C%5C+x%5E2-6x%2B4%3D%28x%2B%5Csqrt%7B5%7D%29%28x-%5Csqrt%7B5%7D%29%3B+%5C%5C+x-1%3D0%2C+x%3D1%3B+%5C%5C++%5Cfrac%7B%28x%2B%5Csqrt%7B5%7D%29%28x-%5Csqrt%7B5%7D%29%7D%7Bx-1%7D%3E0%2C+%5C%5C+%28x%2B%5Csqrt%7B5%7D%29%28x-1%29%28x-%5Csqrt%7B5%7D%29%3E0%2C+%5C%5C+x%5Cin%28-%5Csqrt%7B5%7D%3B1%29%5Ccup%28%5Csqrt%7B5%7D%3B%2B%5Cinfty%29.)
0, \\ x^2-6x+4=0, D_1=5, \\ x_1=3-\sqrt{5}, x_2=3+\sqrt{5}, \\ x^2-6x+4=(x+\sqrt{5})(x-\sqrt{5}); \\ x-1=0, x=1; \\ \frac{(x+\sqrt{5})(x-\sqrt{5})}{x-1}>0, \\ (x+\sqrt{5})(x-1)(x-\sqrt{5})>0, \\ x\in(-\sqrt{5};1)\cup(\sqrt{5};+\infty)." alt=" \frac{x^{2}-6x+4}{x-1}>0, \\ x^2-6x+4=0, D_1=5, \\ x_1=3-\sqrt{5}, x_2=3+\sqrt{5}, \\ x^2-6x+4=(x+\sqrt{5})(x-\sqrt{5}); \\ x-1=0, x=1; \\ \frac{(x+\sqrt{5})(x-\sqrt{5})}{x-1}>0, \\ (x+\sqrt{5})(x-1)(x-\sqrt{5})>0, \\ x\in(-\sqrt{5};1)\cup(\sqrt{5};+\infty)." align="absmiddle" class="latex-formula">
![image](https://tex.z-dn.net/?f=+%5Cfrac%7B3-+x%5E%7B2%7D%7D%7B3+x%5E%7B2%7D-4x-1%7D%3E0%2C+%5C%5C+%0A3-x%5E2%3D0%2C+%5C%5C%0Ax%5E2%3D3%2C+%5C%5C+%0Ax_1%3D-%5Csqrt%7B3%7D%2C+x_2%3D%5Csqrt%7B3%7D%2C+%5C%5C+%0A3-x%5E2%3D-%28x%2B%5Csqrt%7B3%7D%29%28x-%5Csqrt%7B3%7D%29%2C+%5C%5C+%0A3x%5E2-4x-1%3D0%2C+%5C%5C+%0AD_1%3D7%2C+%5C%5C+%0Ax_1%3D%5Cfrac%7B2-%5Csqrt%7B7%7D%7D%7B3%7D+%2C+x_2%3D%5Cfrac%7B2%2B%5Csqrt%7B7%7D%7D%7B3%7D%2C+%5C%5C+%0A3x%5E2-4x-1%3D3%28x-%5Cfrac%7B2-%5Csqrt%7B7%7D%7D%7B3%7D%29%28x-%5Cfrac%7B2%2B%5Csqrt%7B7%7D%7D%7B3%7D%29%3B+%5C%5C+%0A+%5Cfrac%7B-%28x%2B%5Csqrt%7B3%7D%29%28x-%5Csqrt%7B3%7D%29%7D%7B3%28x-%5Cfrac%7B2-%5Csqrt%7B7%7D%7D%7B3%7D%29%28x-%5Cfrac%7B2%2B%5Csqrt%7B7%7D%7D%7B3%7D%29%7D%3E0%2C+%5C%5C%0A%28x%2B%5Csqrt%7B3%7D%29%28x-%5Cfrac%7B2-%5Csqrt%7B7%7D%7D%7B3%7D%29%28x-%5Cfrac%7B2%2B%5Csqrt%7B7%7D%7D%7B3%7D%29%28x-%5Csqrt%7B3%7D%29%3C0%2C+%5C%5C+%0A)
0, \\
3-x^2=0, \\
x^2=3, \\
x_1=-\sqrt{3}, x_2=\sqrt{3}, \\
3-x^2=-(x+\sqrt{3})(x-\sqrt{3}), \\
3x^2-4x-1=0, \\
D_1=7, \\
x_1=\frac{2-\sqrt{7}}{3} , x_2=\frac{2+\sqrt{7}}{3}, \\
3x^2-4x-1=3(x-\frac{2-\sqrt{7}}{3})(x-\frac{2+\sqrt{7}}{3}); \\
\frac{-(x+\sqrt{3})(x-\sqrt{3})}{3(x-\frac{2-\sqrt{7}}{3})(x-\frac{2+\sqrt{7}}{3})}>0, \\
(x+\sqrt{3})(x-\frac{2-\sqrt{7}}{3})(x-\frac{2+\sqrt{7}}{3})(x-\sqrt{3})<0, \\
" alt=" \frac{3- x^{2}}{3 x^{2}-4x-1}>0, \\
3-x^2=0, \\
x^2=3, \\
x_1=-\sqrt{3}, x_2=\sqrt{3}, \\
3-x^2=-(x+\sqrt{3})(x-\sqrt{3}), \\
3x^2-4x-1=0, \\
D_1=7, \\
x_1=\frac{2-\sqrt{7}}{3} , x_2=\frac{2+\sqrt{7}}{3}, \\
3x^2-4x-1=3(x-\frac{2-\sqrt{7}}{3})(x-\frac{2+\sqrt{7}}{3}); \\
\frac{-(x+\sqrt{3})(x-\sqrt{3})}{3(x-\frac{2-\sqrt{7}}{3})(x-\frac{2+\sqrt{7}}{3})}>0, \\
(x+\sqrt{3})(x-\frac{2-\sqrt{7}}{3})(x-\frac{2+\sqrt{7}}{3})(x-\sqrt{3})<0, \\
" align="absmiddle" class="latex-formula">